2004
DOI: 10.1158/0008-5472.can-03-1301
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Induces EP1- and HER-2/Neu-Dependent Vascular Endothelial Growth Factor-C Up-Regulation

Abstract: Cyclooxygenase (COX)-2, the inducible isoform of prostaglandin H synthase, has been implicated in the progression of human lung adenocarcinoma. However, the mechanism underlying COX-2's effect on tumor progression remains largely unknown. Lymphangiogenesis, the formation of new lymphatic vessels, has recently received considerable attention and become a new frontier of tumor metastasis research. Here, we study the interaction between COX-2 and the lymphangiogenic factor, vascular endothelial growth factor (VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
149
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(165 citation statements)
references
References 46 publications
13
149
1
2
Order By: Relevance
“…A similar association between COX-2 and VEGF-C was also demonstrated at the protein levels by immunohistochemical studies of squamous cell carcinomas of the head and neck (Kyzas et al, 2005) and oesophagus (Byeon et al, 2004) as well as in non-small cell lung adenocarcinoma (Su et al, 2004). A role of COX-2 in VEGF-C upregulation was suggested in the case of non-small cell lung cancer cells (Su et al, 2004) as well as oesophageal adenocarcinoma cells (von Rahden et al, 2005). To date, however, no information exists regarding whether COX-2 is causally associated with VEGF-C upregulation and thereby lyphangiogenesis in breast cancer, and if so, what is the role of EP receptors on cancer cells in this event.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…A similar association between COX-2 and VEGF-C was also demonstrated at the protein levels by immunohistochemical studies of squamous cell carcinomas of the head and neck (Kyzas et al, 2005) and oesophagus (Byeon et al, 2004) as well as in non-small cell lung adenocarcinoma (Su et al, 2004). A role of COX-2 in VEGF-C upregulation was suggested in the case of non-small cell lung cancer cells (Su et al, 2004) as well as oesophageal adenocarcinoma cells (von Rahden et al, 2005). To date, however, no information exists regarding whether COX-2 is causally associated with VEGF-C upregulation and thereby lyphangiogenesis in breast cancer, and if so, what is the role of EP receptors on cancer cells in this event.…”
supporting
confidence: 71%
“…Interestingly, a positive association between COX-2 and VEGF-C mRNA expression has been reported in oesophageal adenocarcinoma (von Rahden et al, 2005). A similar association between COX-2 and VEGF-C was also demonstrated at the protein levels by immunohistochemical studies of squamous cell carcinomas of the head and neck (Kyzas et al, 2005) and oesophagus (Byeon et al, 2004) as well as in non-small cell lung adenocarcinoma (Su et al, 2004). A role of COX-2 in VEGF-C upregulation was suggested in the case of non-small cell lung cancer cells (Su et al, 2004) as well as oesophageal adenocarcinoma cells (von Rahden et al, 2005).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Pai and coworkers demonstrated that PGE 2 transactivated EGFR through release of TGFα [9], while another report [11] showed EGFR transactivation that did not depend on extracellular release of growth factors. Other groups have demonstrated transactivation of ErbB receptors, but they did not address whether or not growth factor release was necessary [24,25]. While these reports concur that PGE 2 can transactivate EGFR, they do not agree on the requirement for metalloproteinase activity.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to EP receptors 2-4, we found that over-expressed EP1 did not transactivate EGFR. However, Han and Wu recently demonstrated that an EP1 receptor agonist induced phosphorylation of EGFR and enhanced proliferation and migration of cholangiocarcinoma cells [24], and Su et al showed that PGE 2 transactivated ErbB2 through EP1 [25]. These differing results likely reflect differences between cell lines, opening the possibility that in the correct context, all four EP receptors can transactivate EGFR.…”
Section: Discussionmentioning
confidence: 99%